Efforts to Enhance the Learning of Social Sciences through the Role of the Strategic Factors of Accountability - Njotoprajitno, Rosemarie Sutjiati (EDUCARE, 2011)
ABSTRACT: The urgency to improve the quality of human resources is experiencing continuous escalation. Education holds the key to answer this demand. Social science is an important part of education that is very useful to provide students with various knowledge and skills. In Indonesia, social science tends to be underestimated and many perceived social science as a lesson that only require students to memorize some subject matter without involving further and higher level of thinking. This paper tries to examine the attempt to improve social scienceâs effective learning process through the role of accountabilityâs strategic factors. This research is using quantitative approach through statistical test. The end results show that implementation of accountability in its strategic factors will eventually improve the quality of social scienceâs effective learning process and the graduates. In order to implement and operate an adequate system of accountability, there are various requirements that must be met. Accountability must be thorough and integrated in the institution. Accountability also requires funds and sufficient time for their implementation to demonstrate the expected output. Hopefully, the implementation of accountability in its strategic factors will enhance the dignity, value, and position of social science in order to provide qualified human resources in Indonesiaâs development.KEY WORDS: Social science, human resources, improvement, accountability, strategic factors, and Indonesiaâs development.About the Author: Ir. Rosemarie Sutjiati Njotoprajitno, M.M. is a Lecturer at the Maranatha Christian University in Bandung and Ph.D. Student at the Study Program of Adimistration Education, School of Postgraduate UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. She can be reached at: rosemarie.sutjiati@yahoo.comHow to cite this article? Njotoprajitno, Rosemarie Sutjiati. (2011). âEfforts to Enhance the Learning of Social Sciences through the Role of the Strategic Factors of Accountabilityâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.55-62. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 20, 2011); Revised (July 22, 2011); and Published (August 17, 2011).